Intravascular Ultrasound–Derived Stent Dimensions as Predictors of Angiographic Restenosis Following Nitinol Stent Implantation in the Superficial Femoral Artery. (June 2016) - Miki, Kojiro; Fujii, Kenichi; Kawasaki, Daizo; Shibuya, Masahiko; Fukunaga, Masashi; Imanaka, Takahiro; Tamaru, Hiroto; Sumiyoshi, Akinori; Nishimura, Machiko; Horimatsu, Tetsuo; Saita, Ten; Okada, Kozo; et al.
Purpose: To identify intravascular ultrasound (IVUS) measurements that can predict angiographic in-stent restenosis (ISR) following nitinol stent implantation in superficial femoral artery (SFA) lesions.Methods: A retrospective review was conducted of 97 patients (mean age 72.9±8.9 years; 63 men) who underwent IVUS examination during endovascular treatment of 112 de novo SFA lesions between July 2012 and December 2014. Self-expanding bare stents were implanted in 46 lesions and paclitaxel-eluting stents in 39 lesions. Six months after stenting, follow-up angiography was conducted to assess stent patency. The primary endpoint was angiographic ISR determined by quantitative vascular angiography analysis at the 6-month follow-up. Variables associated with restenosis were sought in multivariate analysis; the results are presented as the odds ratio (OR) and 95% confidence interval (CI).Results: At follow-up, 27 (31.8%) angiographic ISR lesions were recorded. The lesions treated with uncoated stents were more prevalent in the ISR group compared with the no restenosis group (74.1% vs 44.8%, p=0.02). Lesion length was longer (154.4±79.5 vs 109.0±89.3 mm, p=0.03) and postprocedure minimum stent area (MSA) measured by IVUS was smaller (13.9±2.8 vs 16.3±1.6 mm 2, p<0.001) in the ISR group. Multivariate analysis revealed that bare stent use (OR 7.11, 95% CI 1.70 to 29.80, p<0.01) and longer lesion length (OR 1.08, 95% CI 1.01 to 1.16, p=0.04) were predictors of ISR, while increasing postprocedure MSA (OR 0.58, 95% CI 0.41 to 0.82, p<0.01) was associated with lower risk of ISR. Receiver operating characteristic analysis identified a MSA of 15.5 mm 2 as the optimal cutpoint below which the incidence of restenosis increased (area under the curve 0.769).Conclusion: Postprocedure MSA can predict ISR in SFA lesions, which suggests that adequate stent enlargement during angioplasty might be required for superior patency.